More or less ambition in the Doha Round: Winners and losers from trade liberalization with a development perspective - Bouët, Antoine; Mevel, SImon; Orden, David (Wiley, 2007)
What is at stake in the standoff and suspension of the Doha Round of trade talks? What impact would an agreement based on greater or lesser levels of ambition have on developing countries, whose economies are relatively dependent on agriculture? Using the MIRAGE computable general equilibrium model of the global economy, in this article we compare different scenarios for the Doha agricultural and NAMA negotiations, taking real numbers from the proposals on the table from the United States (US) and the European Union (EU) in December 2005. The results for both scenarios demonstrate the high stakes for successful completion of this negotiation given the positions articulated by the countries involved. A cooperative reform outcome by the US and the EU – based on the most ambitious components of their negotiating proposals – delivers noticeably more benefits than an unambitious outcome. We measure the degree of ambition in each scenario by the construction of a Mercantilist Trade Restrictiveness Index and focus the analysis on the impacts on developing countries.